TAXES ON TOBACCO IN SOLVING THE PROBLEMS OF PROMOTING HEALTH OF THE POPULATION - Ольга Ивановна Баран; Юрий Аркадьевич Григорьев (Медицина в Кузбассе)
The progressive increase in taxes on tobacco products plays a huge role in reducing tobacco harm to health of the population. In Russia, the share of the tax burden on the retail tobacco price is still low.